The Design of Electricity Generator Equipment Using Irrigations Water - Hadryanus Simanjuntak; Sumono Sumono; Saipul Bahri Daulay (Universitas Sumatera Utara, 2014)
The development of technology has increased the used of electrical energy in agricultural equipments, so we need an alternatve to supply the requirement of electrical energy by using irrigations line therefore an electricity generator equipment using irrigations water (water mill) was designed.This research was abaut designing each component of the water mill suck as the dimension of the blades, wheels diameter, pulleys diameter and the rate of water flow. Parameters observed were the effective capacity and the manufacturing cost. The result, showed that the effective capacity was 150 wh and the manufacturing cost was Rp 6.000.000,-. Keywords: electricity generator, irrigation line, water mil,